a)(3, 6, 9, 12, 15, ...) = 6 – 3 = 3
b) (5, 3, 1, -1, x, x, ...) =
c) (15, 30, x, ...) = ( 2, 2, 2, x, ...) =
d) (x, 10, 15, 20, x, ...) =
e) (x, -1, -3, -5, x...) =
f) ( 5, 6, 7, x, x, ...) =
g) (x, 12, 18, 24, x, ...) =
Soluções para a tarefa
Respondido por
0
Resposta:
desculpa ñ sei pergunta pra outra pessoa
Explicação passo a passo:
Perguntas interessantes
Física,
7 meses atrás
Matemática,
7 meses atrás
Inglês,
7 meses atrás
Matemática,
7 meses atrás
Português,
7 meses atrás
Biologia,
1 ano atrás
Português,
1 ano atrás